Sa’dallah Wannous: New Aesthetic Sensibilities and Permanent Socio-Political Themes - Harfouch, Mohammad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Sa’dallah Wannous’s oeuvre is divided into three major phases. The third or final phase is marked by aesthetically adventurous theatrical techniques and a new attitude towards human beings, which gives prominence to the individual self, undergoing overwhelming traumatizing experiences. In this paper, an attempt is being made to scrutinize two plays derived from Wannous’s third phase in which history is re-enacted in order to address current burning issues. In Historical Miniatures, the Tamerlane’s invasion of Damascus is depicted, through an epic form, and Rituals of Signs and Transformations, set in 19th Century Damascus, addresses taboo issues, through an experimental structure. In both plays, Wannous has depicted a panorama of a city, with its social spectrum, facing a critical socio-historical reality.